1984
DOI: 10.1073/pnas.81.9.2747
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl oxygen exchange evidence of imine formation in the glutamate dehydrogenase reaction and identification of the "occult role" of NADPH.

Abstract: Although (1), it has generally been assumed that the mechanism of this reaction involves the initial formation of enzyme-bound a-iminoglutarate from a-ketoglutarate and ammonia (N) followed by the reduction of that imine by NADPH in a subsequent step: o NH3 NH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…although the deviations indicate some additional complexity in both the initial and the very late stages of the reaction. 4 Indirect evidence from O 18 exchange studies implicated the involvement of an enzyme R-iminoglutarate-NADPH complex (ERI) as an obligatory intermediate in this reaction (11), and chemical necessity appeared to dictate the requirement of the formation of an R-carbinolamine complex (ERC) as an ensuing step. However, the findings presented here offer the first direct physical evidence of the actual occurrence of these two postulated entities.…”
Section: Substituting the Values Of [Eri] [Erc] And [Erk]mentioning
confidence: 99%
“…although the deviations indicate some additional complexity in both the initial and the very late stages of the reaction. 4 Indirect evidence from O 18 exchange studies implicated the involvement of an enzyme R-iminoglutarate-NADPH complex (ERI) as an obligatory intermediate in this reaction (11), and chemical necessity appeared to dictate the requirement of the formation of an R-carbinolamine complex (ERC) as an ensuing step. However, the findings presented here offer the first direct physical evidence of the actual occurrence of these two postulated entities.…”
Section: Substituting the Values Of [Eri] [Erc] And [Erk]mentioning
confidence: 99%
“…They are grouped into NAD‐specific (EC 1.4.1.2), NADP‐specific (EC 1.4.1.4) and dual [NAD(P)]‐specific (EC 1.4.1.3) forms based on which pyridine nucleotide can serve as the substrate. Regardless of their coenzyme specificity, all GDHs share a common chemical mechanism that invokes a bound ‘iminoglutarate’ intermediate [3–6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the glutamate‐forming reaction proceeds as follows. 2‐OG is firstly converted to 2‐iminoglutarate (2‐IG) through a nucleophilic attack by ammonia, and is then reduced by NADPH to yield glutamate . Therefore, 2‐IG has been proposed as a reaction intermediate; however, the synthesis of this compound by GDH has not yet been directly elucidated due to the low stability of the putative intermediate in aqueous solution.…”
mentioning
confidence: 99%